(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examined 280 boys and girls 4-5 years old living in the city of Urgench and in the Shavat district of the Khorezm region, part of the Southern Aral region. Anthropometric studies of body weight, growth and length of the spine in children were conducted and studied. According to the results of the anthropometric survey, differences in the results of the anthropometric survey of boys and girls 4-5 years old living in rural and urban areas were analyzed. Based on these studies, the physical development of boys and girls 4-5 years old living in urban areas was superior to the physical development of boys and girls 4-5 years old living in rural areas.